Time-varying global energy budget since 1880 from a reconstruction of ocean warming - Quran Wu; Jonathan M. Gregory; Laure Zanna; Samar Khatiwala (Proceedings of the National Academy of Sciences, 2025)
The global energy budget is fundamental for understanding climate change. It states that the top-of-atmosphere imbalance between radiative forcing (which drives climate change) and radiative response (which resists the forcing) equals energy storage in Earth’s heat reservoirs (i.e. the ocean, atmosphere, land, and cryosphere). About 90% of Earth’s energy imbalance is stored as heat content in the ocean interior, which is poorly sampled before 1960. Here, we reconstruct Earth’s energy imbalance since 1880 by inferring subsurface ocean warming from surface observations via a Green’s function approach. Our estimate of Earth’s energy imbalance is consistent with the current best estimates of radiative forcing and radiative response during 1880–2020. The consistency is improved in this study compared to previous ones. We find two distinct phases in the global energy budget. In 1880–1980, Earth’s energy imbalance closely followed the radiative forcing. After 1980, however, Earth’s energy imbalance increased at a slower rate than the forcing; in 2000–2020, the imbalance amounted to less than 50% of the forcing. In simulations of historical climate change, the model-mean energy imbalance is consistent with observations within uncertainties, but individual models with a “weak” response to anthropogenic aerosol agree better with observations than those with a “strong” response. Because the global energy budget before and after 1980 implies very different global warming in the future, further studies are required to better understand the cause of this historical variation.